2019
DOI: 10.3389/fvets.2019.00312
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous Catheter Flow Rates and Ease of Placement at Various Sites in Canine Cadavers

Abstract: Objective: To compare intraosseous catheter placement difficulty, success rates, and flow rates at four different locations in canine cadavers.Design: Prospective study.Setting: Private referral center.Animals: Eleven fresh canine cadavers.Interventions: With owner consent, animals presenting for euthanasia were recruited. Animals received heparin (1,000 IU/kg IV) at least 5 min prior to euthanasia. After euthanasia, EZIO intraosseous catheters were placed into the ilial wing, proximal medial tibia, proximal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
2
8
3
1
Order By: Relevance
“…muscle and fascia) during pressured infusion (up to 300mmH 2 0) seems not unlikely, as shown in experimental animal studies. 19,27,28 This would explain the initial successful IO infusion followed by the subsequent dislocation of the needle. With regard to a suitable and secure emergency IO access, further anatomical studies are needed to determine the accuracy and safety of new alternative puncture areas as described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…muscle and fascia) during pressured infusion (up to 300mmH 2 0) seems not unlikely, as shown in experimental animal studies. 19,27,28 This would explain the initial successful IO infusion followed by the subsequent dislocation of the needle. With regard to a suitable and secure emergency IO access, further anatomical studies are needed to determine the accuracy and safety of new alternative puncture areas as described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased resistance to flow compared to intravenous infusion, reasonably high fluid administration rates can still be achieved with intramedullary delivery ( 158 ). The gravity-dependent rate of fluid delivery was greater in the femur and humerus compared to the tibia and ilium in one canine cadaveric study ( 159 ).…”
Section: Resultsmentioning
confidence: 99%
“…Limitations of placement include need for specialized equipment (except in case of using a hypodermic needle), which may restrict availability. Flow rate is also limited by needle diameter and the bone selected ( 58 ). Contraindications include osteomyelitis, regional pyoderma, preexisting fracture, and orthopedic hardware in the location of interest ( 53 , 54 ).…”
Section: Intraosseous Accessmentioning
confidence: 99%
“…In dogs, successful placement has been described in the proximal humerus, lateral humeral condyle, trochanteric fossa, wing of the ilium, and medial proximal tibia ( 27 , 54 , 58 ). A canine cadaveric study found the proximal humerus and distal femur to have the best combination of high flow rates and ease of access ( 58 ). IO access has also been investigated in cats at the medial tibia and proximal humerus ( 56 ).…”
Section: Intraosseous Accessmentioning
confidence: 99%